Return to Sport After Coracoid Transfer in Athletes With Anterior Shoulder Instability: A Systematic Review - Glogovac, Georgina (Sports Health, 2019)
CONTEXT: Recurrent shoulder instability in young athletes can lead to a spectrum of soft tissue and bony lesions that can be bothersome and/or disabling. Coracoid transfer is a treatment option for athletes with recurrent instability. OBJECTIVE: To report the rate of return to sport for athletes after coracoid transfer. DATA SOURCES: An electronic search of the literature was performed using the PubMed (MEDLINE) and Cochrane Databases (1966-2018). STUDY SELECTION: Studies were included if they evaluated return to sport after treatment with coracoid transfer at a minimum 1-year follow-up. STUDY DESIGN: Systematic review. LEVEL OF EVIDENCE: Level 4. DATA EXTRACTION: Data were extracted by 2 authors and included study design, level of evidence, patient demographics (number, age, sex), procedure performed, duration of clinical follow-up, rate of return to sport, patient-reported outcome measures, reoperations, and complications. RESULTS: Fourteen studies met the inclusion criteria. The rate of return to sport at any level ranged from 80% to 100% in all but 1 study (38%), and the rate of return to the previous level of play ranged from 56% to 95% in all but 1 study (16%). Patients returned to sport at an average of 3.2 to 8.1 months. The average patient-reported outcome scores ranged from 78% to 94% (Rowe), 223.6 to 534.3 (Western Ontario Shoulder Instability Index), and 75% to 90% (subjective shoulder value). The rate of postoperative dislocation ranged from 0% to 14%, and the reoperation rate ranged from 1.4% to 13%. CONCLUSION: There was a high early rate of return to sport in patients who underwent coracoid transfer for anterior shoulder instability, although patients did not reliably return to the same level of play. The procedure had very favorable outcomes for treatment of instability, with low rates of recurrent dislocation and reoperation.